Investigating the role of Epstein-Barr virus and human papillomavirus types 16 and 18 co-infections in cervical disease of Iranian women - Sadeghi, Farzane; Mostaghimi, Talieh; Taheri, Mahdie; Yazdani, Shahla; Javadian, Maryam; Ranaee, Mohammad; Ghorbani, Hossein; Bouzari, Zinatossadat; Sadeghi, Farzin (Frontiers in Oncology, 2024)
Introduction: High-risk human papillomaviruses (HR-HPVs) are known to contribute to cervical cancer (CC), but the role of Epstein-Barr virus (EBV) in this process remains unclear, despite EBV's widespread detection in premalignant and malignant cervical tissues.In this cross-sectional study of 258 cervical samples, including both formalin-fixed paraffin-embedded (FFPE) and fresh cervical tissues, the presence and viral load of HR-HPVs (HPV-16 and HPV-18) and EBV were evaluated in Iranian women with cervical intraepithelial neoplasia (CIN), squamous cell carcinoma (SCC), and a cervicitis control group using real-time PCR.The study revealed a significant correlation between disease severity and both increased HPV-16 positivity and HPV-16 and HPV-18 co-infection (p<0.001).Interestingly, the control group had a higher frequency of EBV-positive cases than SCC/CIN groups (p<0.001). HPV-16 DNA load increased with disease severity (P<0.001), while HPV-18 showed no significant difference (P=0.058). The control group had a higher EBV DNA load compared to SCC/CIN groups (P=0.033). HPV-16 increased the risk of CIN II, CIN III, and SCC, while HPV-18 increased the risk of CIN II and CIN III. Notably, EBV was associated with a lower risk of CIN groups and SCC.No significant difference in EBV co-infection with HPV-16/18 was found, failing to support the hypothesis that EBV is a cofactor in CC. However, high EBV viral load in the control group suggests a potential "hit and run hypothesis" role in CC progression. This hypothesis suggests that EBV may contribute briefly to the initiation of CC with an initial impact but then becomes less actively involved in its ongoing progression.